Deposit Ceilings and Monetary Policy - Benavie, Arthur; Poindexter, J. Carl (The Review of Economics and Statistics, 1973)
SINCE 1966, the Federal Reserve Board has experimented with the use of Regulation Q, the regulation which specifies the maximum interest rates banks are permitted to pay on time and savings deposits, as an active tool of monetary policy. Since September 1966, the Federal Home Loan Bank Board has been empowered to impose ceilings, on savings and loan associations and some mutual savings banks movements in these ceilings to be coordinated with movements in Regulation Q ceilings. In spite of our now-substantial experience with these ceilings, there appears to be no consensus on what purely macro-economic consequences emerge from the employment of deposit ceilings. We need answers to the following two questions: 1) Does the existence of effective deposit ceilings strengthen or weaken standard monetary policy actions? 2) Can the manipulation of deposit ceilings serve as an independent active tool of stabilization policy and, if so, what is the direction of its impact? 1 The official view of the Federal Reserve Board on question (2) appears to be that effective deposit ceilings (attention is typically focused on Q ceilings) are depressive while relaxation of those ceilings is expansionary.2 We know of no clear statement of their position on question (1). There is scant discussion of these issues in the professional literature. In the most general theoretical discussion of deposit ceilings, Tobin (1970) suggests (relying on some casual empirical evidence) that the sign of response of the level of economic activity to changes in interest rate ceilings may vary depending on whether an interest rate variable or a reserve variable is exogenous. He apparently believes that the response we are interested in (letting reserves be held constant) is typically inverse a rise in interest rate ceilings being restrictive. He does not consider question (1). Using a much more restrictive model, Warren Smith (1967) has argued that monetary policy is stronger with effective ceilings (only Q ceilings are considered) than without them. He does not consider question (2). We deal with both questions in this paper. Our analysis suggests that the Tobin and Smith conclusions (on questions (2) and (1), respectively) are incompatible. The model we employ in dealing with these questions differs from both the Smith and Tobin models.3 Our model builds on theirs by incorporating two intermediary claims (both commercial bank time deposits and nonbank intermediary claims), by including currency demand functions, and by considering the impact of incorporation of the price level in the model. Unlike Tobin, we employ the commonplace macro-economic assumption of a single marketable security.4